Escitalopram Ameliorates Cardiomyopathy in Type 2 Diabetic Rats via Modulation of Receptor for Advanced Glycation End Products and Its Downstream Signaling Cascades - Ahmed, Lamiaa A.; Shiha, Nesma A.; Attia, Amina S. (Frontiers in Pharmacology, 2020)
Type 2 diabetes mellitus (T2DM) has been recognized as a known risk factor for cardiovascular diseases. Additionally, studies have shown the prevalence of depression among people with diabetes. Thus, the current study aimed to investigate the possible beneficial effects of escitalopram, a selective serotonin reuptake inhibitor, on metabolic changes and cardiac complications in type 2 diabetic rats. Diabetes was induced by feeding the rats high fat-high fructose diet (HFFD) for 8 weeks followed by a subdiabetogenic dose of streptozotocin (STZ) (35 mg/kg, i.p.). Treatment with escitalopram (10 mg/kg/day; p.o.) was then initiated for 4 weeks. At the end of the experiment, electrocardiography was performed and blood samples were collected for determination of glycemic and lipid profiles. Animals were then euthanized and heart samples were collected for biochemical and histopathological examinations. Escitalopram alleviated the HFFD/STZ-induced metabolic and cardiac derangements as evident by improvement of oxidative stress, inflammatory, fibrogenic and apoptotic markers in addition to hypertrophy and impaired conduction. These results could be secondary to its beneficial effects on the glycemic control and hence the reduction of receptor for advanced glycation end products content as revealed in the present study. In conclusion, escitalopram could be considered a favorable antidepressant medication in diabetic patients as it seems to positively impact the glycemic control in diabetes in addition to prevention of its associated cardiovascular complications.